Poovan banana and the other stories - Vaikkaṃ Muhammad Basheer (Orient BlackSwan, 2009)
This carefully selected collection of Vaikom Muhammad Basheer\\\'s short stories have been translated by V. Abdulla. Basheer\\\'s writings are characterized by a variety of theme and tone. He has enshrined in them every kind of experience from the pangs of hunger and sex to the rapture of mystic vision. Its range includes stark realistic pictures of the material world as well as the realm of fantasy haunted by ghosts and Basheer has written on love and hate, on politicians and pickpockets, on the fancies of childhood and on the disillusionments of adult life with an intense sense of the tragedy of life and at the same time an irrepressible sense of humour.